Psychological detachment in Chinese higher education: a multitheoretical model of academic stress, cultural pressure, and coping resources - Chen, Yingyan; Pan, Lily; Lu, Feifei; Sun, Daokai; Liao, Chuanjing; Na, Meng (Frontiers in Psychology, 2025)
Psychological detachment—the ability to mentally disengage from academic demands during non-study time—remains elusive for Chinese university students, intensified by cultural norms that equate disengagement with weakness and by institutional systems reinforcing constant connectivity. This study integrates the Stressor–Strain–Outcome Model, Conservation of Resources Theory, and Cognitive Appraisal Theory to examine how academic perfectionism, social comparison anxiety, digital burnout, and filial piety stress affect detachment. The mediating roles of resilience, self-esteem, and perceived social support, and the moderating effect of help-seeking stigma, were also tested. A time-lagged survey of 383 students in Zhejiang, analyzed with PLS-SEM, revealed that social comparison anxiety strongly undermines detachment, while digital burnout exerts weaker direct effects but interacts with coping resources. Resilience and self-esteem consistently mediated stressor–detachment links, though stigma diminished their protective effects. These results extend stress-coping theory by showing how cultural obligations and digital immersion constrain recovery in collectivist contexts. The findings highlight the need for resilience training, stigma-reduction initiatives, and digital wellbeing programs. Beyond China, the study underscores how universal stressors such as perfectionism and comparison interact with cultural scripts, offering insights transferable to global higher education.